Acceptance of 3P's (packaging, labeling and grading) regulation among vegetable producers, wholesalers and exporters - Man, Norsida; Mat Daud, Nurul Farhana (2012)
A 3P’s (Grading, Packaging and Labeling) Regulation is a program to improve the quality of agriculture produce through grading, packaging and labeling. The regulations require that all agricultural produce are graded, packaged and labeled before they are marketed (domestic, export or import). The objectives of this program is basically to enhanced the efficiency and effectiveness of the marketing of local produce in order to retain their competitiveness and to maintain current market share to expand both domestic and overseas market access in line with the changes in global trade. The implementation of 3P’s can give the impact on socio economics of the implementers like as productivity, income and value added of produces. However, level of participation, implementation, and effectiveness of extension activities in promoting 3P’s will influence success of the program. The objectives of study are: to examine the respondents profile; to determine the perception and knowledge of 3P’s Regulation; to identify the level of 3P’s practices among the implementers; to clarify extension practices and approach in 3P’s Program. The study targeted vegetable producers (40 respondents) in Pahang and Selangor. The result of the survey reveals that many of the respondents are not yet practicing the 3P’s regulations in full. For labeling especially, the level of implementation of 3P’s is still at low level. This may be due to problem facing the respondents and also lack of knowledge in managing 3P’s practices. The high production cost becomes the most problems face by the respondents. This is because in order to implement 3P, the farmers need more capital to bear the cost of productions. Besides, wholesalers become the important factor in marketing activities and uncertain market price becomes the problems.